Impact Analysis and Development of Collaborative Communication Models in Public Relations Programs for Mangrove Conservation - Vincentius Varrel; Novianty, Siti Juhriah; Hanutama, Paundra (Ilomata International Journal of Social Science, 2024)
Mangrove forests, as coastal ecosystems, play a crucial role in maintaining the sustainability of fishery resources and protecting shores from erosion and storms. However, mangrove degradation continues to escalate, primarily due to human activities such as shrimp pond expansion and uncontrolled logging. Public Relations programs can serve as effective tools to raise awareness and engage communities in mangrove conservation. Impact analysis and the development of a collaborative communication model are key to understanding the effectiveness of such programs. This research aims to analyze the impact of the Public Relations program on mangrove conservation and develop a more effective collaborative communication model. The focus is on understanding behavioral changes, community responses, and the program's contribution to the sustainability of the mangrove ecosystem. The research methodology employed is qualitative-descriptive with an impact analysis approach. Interviews with representatives from local communities, local governments, non-governmental organizations, and Public Relations practitioners were conducted to gather data. Content analysis was also performed on the program's communication materials. The research findings indicate that the Public Relations program has positively impacted the increase in community awareness and behavioral changes related to mangrove conservation. However, challenges persist concerning environmental uncertainties and the lack of participation from certain segments of the community. A collaborative communication model integrated with mangrove conservation theories, impact analysis, and community engagement proves essential for further improvement. The implications of this research reflect the importance of impact analysis and developing collaborative communication models in Public Relations programs for mangrove conservation. These findings underline that active collaboration with various stakeholders is key to ensuring the sustainability of mangrove ecosystems.